Решите уравнение (x+2)(x^2-2x+4)-x(x-3)(x+3)=26 помогите плиззз

0 голосов
22 просмотров

Решите уравнение
(x+2)(x^2-2x+4)-x(x-3)(x+3)=26
помогите плиззз


Алгебра (20 баллов) | 22 просмотров
0

помогите!!!!!!!!!sos!sos!!

Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

(x+2)(x^2-2x+4)-x(x-3)(x+3)=26 \\ x^3+8-x(x^2-9)=26 \\ x^3+8-x^3+9x=26 \\ 9x=18 \\ x=2
(80.5k баллов)
0 голосов
(x+2)(x^2-2x+4)-x(x-3)(x+3)=26
(x+y)(x^2-xy+y^2)=x^3+y^3
x^2-y^2=(x-y)(x+y)
(x+2)(x^2-2x+2^2)- x(x^2-9)=26
x^3+8 - x^3 + 9x =26
8+9x=26
9x=18
x=2
(10.4k баллов)
0

Откуда "У"

0

пример как решит